Combined effects of added beta glucan and black tea in breads on starch functionality - M Jalil, A.; Edwards, Christine; Combet, E.; Ibrahim, M.; Garcia, A. (Informa Healthcare, 2015)
Bread and tea are usually consumed separately, but there may be different food-matrix interactions and changes in starch characteristics when they are combined in bread. This study developed breads (white bread, WF; black tea, BT; beta glucan, ßG; beta glucan plus black tea, ßGBT) and determined their starch functionalities. Breads were developed using a standard baking recipe and determined their starch characteristics. There was no significant difference in starch hydrolysis between BT and WF but ßGBT reduced early (10min) starch hydrolysis compared with ßG. The starch granules in ßG and ßGBT were elliptical and closely packed together. These results suggest that the addition of beta glucan and black tea to bread preserved the elliptical starch granules and lowered short-term starch hydrolysis.